Portal Vein Glucose Sensors Do Not Play a Major Role in Modulating Physiological Responses to Insulin-Induced Hypoglycemia in Humans - Rossetti, Paolo (American Diabetes Association, 2009)
OBJECTIVE—Experimental data from animal studies indicate that portal vein glucose sensors play a key role in the responses to slow-fall hypoglycemia. However, their role in modulating these responses in humans is not well understood. The aim of the present study was to examine in humans the potential role of portal vein glucose sensors in physiological responses to insulin-induced hypoglycemia mimicking the slow fall of insulin-treated diabetic subjects. RESEARCH DESIGN AND METHODS—Ten nondiabetic subjects were studied on two different occasions during intravenous insulin (2 mU · kg(−1) · min(−1)) plus variable glucose for 160 minutes. In both studies, after 60 min of normal plasma glucose concentrations, hypoglycemia (47 mg/dl) was induced slowly (60 min) and maintained for 60 min. Hypoglycemia was preceded by the ingestion of either oral placebo or glucose (28 g) given at 30 min. RESULTS—Plasma glucose and insulin were not different with either placebo or glucose (P > 0.2). Similarly, counterregulatory hormones, substrates, and symptoms were not different with either placebo or glucose. The Stroop color and colored words subtest of the Stroop test deteriorated less (P < 0.05) with glucose than placebo. CONCLUSIONS—In contrast to animals, in humans, prevention of portal hypoglycemia with oral glucose from the beginning of insulin-induced slow-fall hypoglycemia has no effect on sympathoadrenal and symptomatic responses to hypoglycemia.